2019
DOI: 10.4102/sajpsychiatry.v25i0.1372
|View full text |Cite
|
Sign up to set email alerts
|

First-episode psychosis and substance use in Nelson Mandela Bay: Findings from an acute mental health unit

Abstract: BackgroundUse of psychoactive substances is a common finding in studies on first-episode psychosis (FEP), and this has prognostic implications. We know very little about psychoactive substance use (SU) among patients with FEP in the Eastern Cape province (EC) of South Africa (SA).AimThe study seeks to determine SU prevalence and associated features among inpatients with non-affective FEP in an acute mental health unit (MHU) in Nelson Mandela Bay, EC.SettingResearchers conducted a retrospective clinical file re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
(54 reference statements)
2
16
1
Order By: Relevance
“…In South Africa, variable prevalence rates of SUD amongst psychiatric inpatients have been found. 10,14,29,30,31 Our results are similar to the 62% prevalence of a current SUD found amongst acute psychiatric patients in the Western Cape, 29 and to the 72% prevalence found amongst a sample of Gauteng state patients. 14 Using the ASSIST questionnaire in a study at a regional psychiatric hospital in KwaZulu-Natal, South Africa, 22 patients were reported to have a similar 54% recent alcohol use and 43% recent cannabis use.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In South Africa, variable prevalence rates of SUD amongst psychiatric inpatients have been found. 10,14,29,30,31 Our results are similar to the 62% prevalence of a current SUD found amongst acute psychiatric patients in the Western Cape, 29 and to the 72% prevalence found amongst a sample of Gauteng state patients. 14 Using the ASSIST questionnaire in a study at a regional psychiatric hospital in KwaZulu-Natal, South Africa, 22 patients were reported to have a similar 54% recent alcohol use and 43% recent cannabis use.…”
Section: Discussionsupporting
confidence: 84%
“…However, the prevalence in our sample was less than the 81.2% found amongst patients admitted with first episode psychosis in the Eastern Cape. 30 Substance use disorder has been shown to be more common with first episode psychosis than with subsequent episodes. 32 Index psychiatric presentations were not frequent amongst those with SUD in our sample; however, if the 60 participants with an index psychiatric presentation were considered separately, then 75% ( n = 45) had a SUD, bringing the prevalence rate closer to that found in the Eastern Cape study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamines (tik, speed), cocaine (coke, crack, rock), and opiates each had a prevalence of use of 0.3% [8]. Authors [27] Thungana et al (2019) reported a prevalence of 81.9% among individuals admitted with first-episode psychosis (FEP) in the Nelson Mandela Bay of Eastern Cape Province. Findings of Thungana et al (2019) are limited to people with FEP and do not reflect the broader categories of mental illnesses managed at the province's health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…The same argument made for integrated addictions treatment has given the high rates of substance abuse in our setting, not just amongst patients with psychotic disorders but the general population as well. 41 , 42 Further research is therefore needed to validate the low levels of evidence (opinion) for these interventions in low resource settings. This study however may form a basis for the development of SEIS for psychotic disorders in the region.…”
Section: Discussionmentioning
confidence: 99%